Comparison of diagnostic informative value of the methods for the determination of direct (hyaluronic acid) and indirect (alanine aminotransferase, aspartate aminotransferase, de Rithis coefficient) of liver fibrosis markers in patients with chronic viral hepatitis C - L. V. Moroz; I. Yu. Bondaruk (Kazimierz Wielki University, 2019)
The results of chronic viral hepatitis C patients examinations are described. A comparative characteristic of the diagnostic informative value of direct (hyaluronic acid) and indirect (alanine aminotransferase, aspartate aminotransferase, de Ritis coefficient) of liver fibrosis markers by the use of ROC - analysis is presented. The objective: to explore the possibility of non-invasive methods for diagnosing liver fibrosis in patients with chronic viral hepatitis C (CVH C). Materials and methods. 66 CVH C with the 1st genotype of the virus were examined. They were either at dispensary observation or ambulatory treatment at Municipal Clinical Hospital №1 (Vinnitsa, Ukraine) and in the clinical department of viral hepatitis at L. V. Gromashevsky Institute of Epidemiology and Infectious Diseases of NAMS (Ukraine). All patients underwent fibroelastography (FEG) on the METAVIR fibrosis score. In all CVH C patients and control group individuals content of hyaluronic acid (HA) in blood serum was determined. ELISA method and "Hyaluronic Acid" kit (Corgenix, Inc., USA) were used. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity was investigated with kinetic method (analyzer and test system Cobas 6000, Roche Diagnostics, Switzerland). Results: AUC for HA content in serum of CVH C patients was in the range 0.720-0.917 (p